The challenge of competencies in training for educational research: a conceptual approach - Cristian Velandia Mesa; Francisca José Serrano Pastor; María José Martínez Segura (Universidad de Costa Rica, 2019)
This article shows the results of the study, which purpose was to reconfigure and develop a conceptual approach to research competences for the strengthening of educational research training processes. The research was conducted in four academic semesters and was based on a mixed approach with a Sequential Transformative Research Design (DITRAS). The process included a stage of documental analysis and systematization of qualitative data that were collected through semi-structured interviews. The second stage included the implementation of the CMI technique, which purpose was to identify categorical systems to classify research competences through the analysis of hierarchical conglomerates. Eleven experts in the area of ​​teaching-research in Higher Education participated, 24 students and 4 alumni from an undergraduate program in Early Childhood Education. The result of the study was to build a conceptual and taxonomic approach to the competencies for teacher-researcher training, which includes 79 learning outcomes that are classified in 29 constructs, and related in 8 competences. The strong theoretical influence in the processes of research training, the gradual devaluation of the experience as an agent in the construction of knowledge, and the pedagogical practice focused on the instrumentalization represent new challenges that go beyond the methodological. These challenges focus on the development of research training processes based on ethics, technology, teamwork and innovation. The final reflections constitute an approach to rethink the academic curricula based on formative research as an agent of transformation and assurance of educational quality.